THE USE OF COMMUNITY LANGUAGE LEARNING (CLL) IN TEACHING SPEAKING - Irwandi Irwandi (Muhammadiyah University of Mataram, 2015)
The purpose of this research is to find out the effectiveness of using CLL in teaching speaking at the first grade students of SMP N 18 Mataram in academic year 2014 / 2015. This is kind of quantitative research with quasi experimental method. The population of this research involved 67 students’ from the first grade in SMPN 18 Mataram. The reseacher took 44 students as a sample that divided into two groups, 22 students belong to the experimental group and 22 students belong to the control group. To find out the differences of x and y, the writer used pre- test and post- test to collect the data. The data collected was analized by t-test formula. Therefore, the writer gave different treatment to prove that CLL is better than conventional method. After the writer gave the treatment, it showed that the mean of post test of experimental group is higher than control group. After that, the result of mean score of Experimental and group is proved by the t-test and compared with t-table, so the result in t-test is 3,8 and t-table (0,05%) is 2,02 and (0,01 %) is 2,70. In addition, the result of the t-test is higher than t-table (3,8 > 2.02 > 2,70). This means that there is significant different between experimental and control group. From the explanation above, the writer concludes that Community Language Learning (CLL) was effective in teaching speaking for the first grade students of SMP N 18 Mataram in academic year of 2014/2015.